Perancangan Sistem Informasi Penjualan pada One Mebel Menggunakan Metode Rapid Application Development (RAD) Berbasis Web - Fazar Octavian Pradana; Entis Sutisna (CV. Multi Kreasi Media, 2022)
The rapid development of a trading business or industry at this time makes information a very important role in supporting the course of sales operations. At the One Mebel which is engaged in the industry that was established in 2010 it is still done conventionally, therefore an online sales system is designed using sales promotion media with the aim of increasing sales volume so that store revenue increases. The method used in this research is Rapid Application Development (RAD) because the application developed is a simple application and does not require a long time to develop. Because the RAD method supports designing applications in a short period of time. After designing, implementing, and testing the Web-Based Sales Information System at One Mebel Using the Rapid Application Development (RAD) method, it can be concluded that this system can solve existing problems, namely This sales information system designed has a feature where you can view and monitor item data and sales reports, making it easier for employees from the One Mebel.